Loneliness and Aggression of the Adolescents in Chittagong (Chittagong University Journal of Biological Sciences, 2024)
Adolescence is a period of stress and storm in which adolescents have to adjust with different physical, social, and psychological changes. If any adolescent fails to cope with these changes, then they may undergo various psychological challenges such as loneliness, aggression, emotional instability, etc. The present study aimed to know the nature of loneliness and aggression among adolescents as a function of adolescents developmental stages, medium of institution, and gender.120 participants were selected purposively in the age range 10-21 years (M=15.5±3.61). The present study showed that early adolescents scored more loneliness than the middle and late adolescents (F (2,108) =154.83, p